Analysis of efficiency of sidewalks as ecological sustainable drainage system in urban centers: case study in Flamboyant Park, Goiânia –Goiás - Santos, Layara de Paula Sousa; Cuba, Renata Medici Frayne; Leitão, Valéria de Sousa; Santos Neto, Agenor de Sousa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Increasing urbanization and soil sealing are among the main factors that affect the flow of rainwater, thus increasingly frequent becomes the occurrence of floods and flooding. In this context the urban drainage is an essential function: to minimize the presence of movement of excess water, especially rain in improper places in urban areas. This research addressesthe importance of use of sustainable drainage systems in order to reduce problems such as flooding and commitments of waterways. Thus, the overall objective is to investigate the environmental contribution of the ecological sidewalks in the Flamboyant Park region located in the urban area of Goiânia -Goiás. For data collection, were made library research, field surveys with photographic records, consultation with agencies Public and infiltration test conducted in the Park to check theefficiency of permeability of interlocking pavements. The results of the tests showed satisfactory values floors in view of waterproof locations.